2002
DOI: 10.1007/s00432-002-0327-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent differences in tumor cell polarity in endometrial carcinomas

Abstract: These findings indicate that in endometrial carcinomas, the age-dependent differences in tumor cell polarity may be related to status of endogenous ovarian hormones, closely linked with cell proliferation and some prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Asian populations, a study conducted in Taiwan revealed a higher incidence of endometrioid carcinoma and lower rates of DMI and LVSI in patients under 50 years old [ 16 ]. The distinct clinical characteristics of younger patients could indicate the biological and genetic diversity of endometrial cancer across various age groups [ 5 , 17 ]. Overall, the previous results showed consistency in certain features, including less DMI and lower grades.…”
Section: Discussionmentioning
confidence: 99%
“…In Asian populations, a study conducted in Taiwan revealed a higher incidence of endometrioid carcinoma and lower rates of DMI and LVSI in patients under 50 years old [ 16 ]. The distinct clinical characteristics of younger patients could indicate the biological and genetic diversity of endometrial cancer across various age groups [ 5 , 17 ]. Overall, the previous results showed consistency in certain features, including less DMI and lower grades.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also indicated high p27 expression in endometrial carcinomas adjacent to secretory non-neoplastic endometrium as compared to those surrounded by atrophic or proliferative tissues. 40) Considering that GSK-3β activity is altered by progesterone, 33) it is thus possible that stabilization of β-catenin and p27 in response to progesterone may occur in parallel through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…22,38 Thus, distinguishing normal glandular endometrium from well-differentiated adenocarcinoma using 3D culture might not be possible by assessing only gross morphological criteria. Interestingly, endometrial tumors show age-dependent differences in polarity based on parameters such as the position of the cell nucleus and the formation of glandular convolution, 39 with abundance of nonpolarized neoplasms in older patients. This observation suggests that apical polarity might be an important feature to scrutinize for the classification of endometrial neoplasia.…”
Section: D Cultures To Develop Diagnostic Tools For Neoplasiamentioning
confidence: 99%